PENERAPAN BLENDED LEARNING DENGAN MOODLE DAN MEDIA WEBSITE DALAM PEMBELAJARAN JURNALISTIK DARING - dan Irfai Fathurohman, Muhammad Noor Ahsin (Sasando, 2020)
Learning to write news in online journalism courses in the Indonesian Language and Literature Education Program, University of Muria Kudus is difficult for students. Students also have difficulty uploading articles on online news portals. To overcome this problem, online journalism learning implements blended learning, which combines face-to-face learning and online learning with Sunan's e learning using the Moodle application and the online news portal website media, kudusnet.com. This research is a classroom action research. The research subjects were 19 students who took online journalism courses, semester V. The data were obtained by means of test techniques, document review, interviews, and questionnaires. The results showed that the students' ability to write news with the percentage of student completeness reached 52.6% in the first cycle, in the second cycle it increased to 89.5%. The ability of students to post articles on the website has also improved.